Right Compared With Left Thoracic Approach Esophagectomy for Patients With Middle Esophageal Squamous Cell Carcinoma - Zheng, Yan; Li, Yin; Liu, Xianben; Zhang, Ruixiang; Sun, Haibo; Xing, Wenqun (Frontiers in Oncology, 2020)
Background: The open surgical approaches for esophageal cancer(EC) can be mainly divided into the right and left transthoracic approach in China. Although it shows an increasing number of right side approach, the optimal surgical technique remains unclear. This study attempt to compare the long-term survival between two approaches in a large cancer center with rich experience of both side transthoracic approach. Methods: The patients who underwent right transthoracic approach esophagectomy(Right, McKeown) and left transthoracic approach esophagectomy(Left, Sweet or chest neck dual-incision) for esophageal squamous cell carcinoma(ESCC) during January 2015 to October 2018 were included. The overall survival(OS) rate and perioperative data between two groups were retrospectively analysed. Results: We included 437 patients who underwent Right(n=202) and Left(n=235) approach for ESCC. There was a significantly longer median operative time(250 min vs. 190 min, P<0.001) and longer median postoperative hospital stady days(17 days vs. 14 days, P<0.001) in Right groups. The OS at 5-years was 49.9% and 52.45% in Right and Left groups, respectively; hazard ratio(HR)(95% CI): 1.002(0.752–1.337), p=0.987. Conclusions: For middle thoracic ESCC without suspected lymph node metastasis in the upper mediastinum, the esophagectomy through left thoracic approach could achieve the same OS with right side, and better short-term outcomes.